Zambia : Issues of Scaling Up in Peri-Urban Areas - Garrett, James (World Bank, Washington, DC, 2012)
This note is part of a series that examines the factors that facilitate the scaling up of Community Driven Development (CDD) programs. The note highlights the experience of CARE Zambia's Program of Support for Poverty Elimination and Community Transformation (PROSPECT) initiative, which applies a community based approach to reduce poverty in peri-urban areas of Lusaka, and discusses the importance of linking CDD with structures, and processes outside community boundaries, to ensure that they are able to scale up in more dynamic and sustainable ways than simple replication. It also examines the difficulties of doing so in the face of opposition by entrenched political interests.